PENGARUH BAURAN PROMOSI TERHADAP MINAT BELI KONSUMEN (Studi Kasus Pada PT. Capella Dinamik Nusantara Ujungbatu) - Rita, Lusi Maretti; Sutrisna, Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research have done in PT. Capella Dinamik Nusantara Ujungbatu, and the purpose of this research is to know the influence promotion mixed towards buying interest customers of PT. Capella Dinamik Nusantara Ujungbatu. Promotion mixed as independent variable (X) while the customers buying interest as dependent variable (Y).The problem of this research is decline realization sales of PT. Capella Dinamik Nusantara Ujungbatu then target unappropriate with realization sales. There has been seen from realization sales percentage which is fluctuated or up and down the purchase of motor cycle for last 5 years. Sample of this research is taken about 96 slovin formula. The data has been obtained from questionnaire and process next to making a test with statistic by SPSS program. The result of the calculation is the promotion mixed has positive effect about 72,5 % towards customers buying interest in PT. Capella Dinamik Nusantara UjungbatuKeywor: Promotio Mixed, Customers Buying Interest